2003
DOI: 10.1016/j.foodpol.2003.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Realigning research and extension to focus on farmers’ constraints and opportunities

Abstract: This paper argues that research and extension have failed to (1) develop technologies that take into account farmers' resource constraints and risks; and (2) improve farmers' capacity to adapt technologies to their own situations. The paper critiques continued use of blanket, high-dose fertilizer recommendations, arguing for approaches that teach farmers how to maximize returns from smaller, more affordable input purchases. Developing such technologies requires that researchers integrate a wider range of stake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 16 publications
0
43
0
Order By: Relevance
“…Continued evaluation of results with farmers led to the inclusion of large rates and combinations of small and large rates of fertilizer in comparison with the low rates of manure and fertilizer, therefore increasing options for the farmers. The process showed that there is a valid argument in encouraging research to focus on technologies that take into account farmer's constraints and improve farmer's capacity to adapt technologies to their own situations (Snapp et al 2003;Dimes et al 2004a, b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Continued evaluation of results with farmers led to the inclusion of large rates and combinations of small and large rates of fertilizer in comparison with the low rates of manure and fertilizer, therefore increasing options for the farmers. The process showed that there is a valid argument in encouraging research to focus on technologies that take into account farmer's constraints and improve farmer's capacity to adapt technologies to their own situations (Snapp et al 2003;Dimes et al 2004a, b).…”
Section: Discussionmentioning
confidence: 99%
“…The poor adoption of improved fertility management methods is attributable to several reasons, including: (i) inappropriate recommendations that fail to consider rainfall risks and investment capacity of smallholder farmers, (ii) blanket recommendations that overlook the spectrum of farming objectives and returns on investment that typifies smallholder farming systems, and (iii) inappropriate marketing of fertilizers to smallholder farmers (Dimes et al 2004a, b). Several authors have made the case for fertility options rather than blanket recommendations that do not take into account the local variability in soil fertility (Giller et al 2006) and largely ignore socioeconomic factors (Ahmed et al 1997;Rohrbach 1999;Snapp et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the weak link between research and extension is a problem characteristic of developing countries (Anandajayasekeram, Ranjitha, Sindu, & Dirk, 2008). There is evidence of inadequate technological messages from rural extension services (Snapp et al, 2003;Cunguara & Moder, 2011). At the root of this weak link between extension and agrarian research is the scarcity of resources on the part of these two institutions (Gemo, Eicher, & Teclemariam, 2005).…”
Section: Institutional Framework Partnerships and Support For Agrarimentioning
confidence: 99%